Delivering kidney cancer care in rural Central and Southern Illinois: a telemedicine approach. (7th October 2014) - Alanee, S.; Dynda, D.; LeVault, K.; Mueller, G.; Sadowski, D.; Wilber, A.; Jenkins, W.D.; Dynda, M.
<x xml:space="preserve">Abstract</x> There is a growing body of experience and research suggesting that telemedicine (video conferencing, smart phones and online patient portals) could be the solution to addressing gaps in the provision of specialised healthcare in rural areas. The proposed role of telemedicine in providing needed services in hard to reach areas is not new. The United States Telecommunication Act of 1996 provided the initial traction for telemedicine by removing important economic and legal obstacles regarding the use of technology in healthcare delivery. This initial ruling has been supplemented by the availability of federal funding to support efforts aimed at developing telemedicine in underserved areas. In this paper, we explore one aspect of disease disparity pertinent to rural Illinois (kidney cancer incidence and mortality) and describe how we are planning to use an existing telemedicine program at Southern Illinois University School of Medicine (SIUSOM) to improve kidney cancer (Kca) care in rural Illinois. This represents an example of the possible role of telemedicine in addressing healthcare disparities in rural areas/communities and provides a description of general challenges and barriers to the implementation and maintenance of such systems.